2004
DOI: 10.1186/1471-2229-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of induced point mutations in maize genes by TILLING

Abstract: BackgroundGoing from a gene sequence to its function in the context of a whole organism requires a strategy for targeting mutations, referred to as reverse genetics. Reverse genetics is highly desirable in the modern genomics era; however, the most powerful methods are generally restricted to a few model organisms. Previously, we introduced a reverse-genetic strategy with the potential for general applicability to organisms that lack well-developed genetic tools. Our TILLING (Targeting Induced Local Lesions IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(113 citation statements)
references
References 36 publications
5
107
0
1
Order By: Relevance
“…Establishment of a high throughput SNP detection system for mutant screening In this study, non-labeled primers were used for ampliWcation of the target sequence in the genome by PCR, instead of Xuorescence-labeled primers that have been used for TILLING in several plants (Slade et al 2005;Till et al 2003Till et al , 2004Till et al , 2007Wu et al 2005). Heteroduplex molecules were formed from the PCR ampliWcation by denaturation and re-annealing of a pooled sample containing both wildtype and mutant DNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment of a high throughput SNP detection system for mutant screening In this study, non-labeled primers were used for ampliWcation of the target sequence in the genome by PCR, instead of Xuorescence-labeled primers that have been used for TILLING in several plants (Slade et al 2005;Till et al 2003Till et al , 2004Till et al , 2007Wu et al 2005). Heteroduplex molecules were formed from the PCR ampliWcation by denaturation and re-annealing of a pooled sample containing both wildtype and mutant DNA.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated in several organisms (Gilchrist and Haughn 2005;Haughn and Gilchrist 2006;HenikoV et al 2004). In plants, TILLING combined with ethylmethanesulfonate (EMS)-mutagenesis has been used successfully to screen mutant populations induced in Arabidopsis thaliana, and has recently been extended to mutation screening in crops using EMS and/or other chemical mutagens (Caldwell et al 2004;Slade et al 2005;Till et al 2004Till et al , 2007Wu et al 2005). Till et al (2007) have very recently reported high performance mutation screening in the EMS and Az-MNU treated mutant populations of japonica rice cv.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, high-throughput mutagenesis programs were launched to both expand this inventory of maize mutants and expedite the distribution of mutants to the research community (Table 1). For example, the Maize TILLING (Targeting Induced Local Lesions IN Genomes) project is a reversegenetics approach utilizing gene-targeted screening of EMS-mutagenized inbred populations (Till et al 2004;Weil and Monde 2007). A second project involves the use of the Activator (Ac)/Dissociation (Ds) transposable element system in a strategy of targeted, regional mutagenesis.…”
Section: Genetics and Genomicsmentioning
confidence: 99%
“…Additional transposon mutagenesis and TILLING projects that are underway for many crop species will serve as an excellent source for more such mutants, especially when they are in uniform, well-characterized backgrounds Till et al, 2004). Transgenic dominant negative (RNAi) or overexpression mutants will also be particularly valuable starting material, revealing QTLs for the trait of interest in a single generation, just as dominant genetic mutations do (Fig.…”
Section: Discussionmentioning
confidence: 99%